Remimazolam Requires Less Vasopressor Support during Induction and Maintenance of General Anesthesia in Patients with Severe Aortic Stenosis Undergoing Transcatheter Aortic Valve Replacement: A Retrospective Analysis from a Single Center. (22nd October 2022) - Miyoshi, Hirotsugu; Watanabe, Tomoyuki; Kido, Kenshiro; Kamiya, Satoshi; Otsuki, Sachiko; Narasaki, Soshi; Toyota, Yukari; Kondo, Takashi; Horikawa, Yousuke T.; Saeki, Noboru; Tsutsumi, Yasuo M.
Abstract : Introduction. We compared the hemodynamics during general anesthesia with remimazolam and conventional anesthetics in patients with severe aortic stenosis (AS). Methods. This was a retrospective single-center analysis. We reviewed the records of 42 patients who underwent transcatheter aortic valve implantation with a transfemoral artery approach under general anesthesia from January to December 2020. Patients were divided into three groups based on the general anesthetic used for (induction/maintenance) remimazolam/remimazolam (Group R/R), propofol/sevoflurane (Group P/S), and midazolam/propofol (Group M/P). Vasopressor use (ephedrine, phenylephrine, and noradrenaline) was compared among the groups. Results. The number of patients in each group was 15 (Group R/R), 13 (Group P/S), and 14 (Group M/P), with no significant difference in background characteristics and intraoperative vital signs. For anesthesia induction, doses of ephedrine and phenylephrine used were significantly lower in Group R/R (ephedrine [mg]: Group R/R 2 [0–4] vs. Group P/S 8 [8–12], P < 0.001, Group R/R vs. Group M/P 5 [0–15], P = 0.39 ; phenylephrine (mg): Group R/R 0 [0–0.08] vs. Group P/S 0.15 [0.10–0.20], P = 0.03, Group M/P 0.21 [0.04–0.40], P = 0.08 ). For anesthesia maintenance, the noradrenaline dose used was low in the Group R/R (noradrenaline [ μ g/kg/min]: Group R/R 0.019 [0.015–0.039], Group P/S 0.042 [0.035–0.045], P = 0.02, Group M/P 0.048 [0.040–0.059], P < 0.01 ). Conclusion. In patients with severe AS, induction and maintenance of anesthesia with remimazolam resulted in less overall vasopressor use than conventional general anesthetics.